Respons Pertumbuhan Bibit Kelapa Sawit (Elaeis guineensis Jacq.) terhadap Pemberian Pupuk Organik Asal Pelepah Kelapa Sawit dan Pupuk Majemuk NPK - Mira Ariyanti; Gita Natali; Cucu Suherman (Agrikultura, 2017)
ABSTRACTThe growth response of oil palm (Elaeis Guineensis Jacq.) seedling toward the application of organic fertilizer from palm fronds and NPK compound fertilizerThe research was aimed to study the influence between organic fertilizers from palm fronds and NPK compound fertilizer to reduce NPK compound fertilizer in main nursery. The experiment was conducted from January to April 2017 at the Experiment Station Ciparanje, Faculty of Agriculture, Universitas Padjadjaran. The experimental design used was Randomized Block Design that arranged in factorial patterns with two factors and three replications. The fisrt factor was dosage of organic fertilizers from palm fronds consisted of three levels of 0 g/polybag, 800 g/polybag, and 1600 g/polybag and the second factor was dosage of NPK compound fertilizer consisted of four levels of 0 g/polybag, 20 g/polybag, 40 g/polybag, and 60 g/polybag. The result of the experiment showed that there was interaction effect between organic fertilizers from palm fronds and NPK compound fertilizer on height of seedling and dry weight of the shoot. The dosage of 1600 g/polybag organic fertilizers from palm fronds with the dosage of 20 g/polybag NPK compound fertilizer showed the best result in dry weight of the shoot.Keywords: Oil palm seedling, Main nursery, Organic fertilizer, Palm frond, NPK compound fertilizerABSTRAKPenelitian ini bertujuan untuk mengetahui pengaruh interaksi antara pupuk organik asal pelepah kelapa sawit dengan pupuk majemuk NPK yang baik untuk mengurangi penggunaan pupuk majemuk NPK di pembibitan utama kelapa sawit. Percobaan dilaksanakan dari bulan Januari sampai dengan April 2017 di Kebun Percobaan Ciparanje, Fakultas , Universitas Padjadjaran. Rancangan percobaan yang digunakan adalah Rancangan Acak Kelompok dengan pola faktorial yang diulang sebanyak tiga kali. Faktor pertama meliputi dosis pupuk organik asal pelepah kelapa sawit terdiri dari tiga taraf yaitu 0 g/polybag, 800 g/polybag, dan 1600 g/polybag dan faktor kedua dosis pupuk majemuk NPK yang terdiri empat taraf yaitu 0 g/polybag, 20 g/polybag, 40 g/polybag, dan 60 g/polybag. Hasil percobaan menunjukkan bahwa terdapat pengaruh interaksi pupuk organik asal pelepah kelapa sawit dengan pupuk majemuk NPK terhadap tinggi tanaman dan bobot kering tajuk. Perlakuan pupuk organik asal pelepah kelapa sawit 1600 g/bibit dengan pupuk majemuk NPK 20 g/bibit menghasilkan bobot kering tajuk bibit kelapa sawit terbaik.Kata Kunci: Bibit kelapa sawit, Pembibitan utama, Pupuk organik, Pelepah kelapa sawit, NPK